Pemetaan Penelitian Bioteknologi terkait Vaksin Covid-19 dan Kontribusi Indonesia: Analisis Bibliometrik selama Pandemi Covid-19 Tahun 2020 - Firman Fajar Perdhana (UIN Sunan Gunung Djati Bandung, 2021)
The Covid-19 pandemic, which is currently threatening humanity, has led to research explosions all over the world, including in Indonesia. Various biotechnology studies on Covid-19 vaccine has not been mapped globally, open the potential for overlapping or research vacancies in certain areas. This study aims to analyze biotechnology research on Covid-19 vaccine and find out the contribution of Indonesian researchers in scientific publication during the Covid-19 pandemic in 2020. A total of 1777 refined documents on topics of biotechnology, Covid-19, SARS-CoV-2, and vaccine were collected from the Scopus database without any limitations. All documents were determined their bibliometric characteristics, including document type, source title, the most productive countries and institutions, top authors, and top citations. The most document type was article-based documents (911 documents). The Journal of Biomolecular Structure and Dynamics was the leading source with 80 documents. The United State of America was the most productive country with 427 publications, followed by India (383) and China (237). The Chinese Academy of Science was the most productive institution with 34 publications, followed by the Ministry of Education China and the National Institute of Health, both with 28 publications. Indonesia ranked the 26th, contributed 23 publications. Bibliometric visualization resulted in four major clusters: (1) the study related to Covid-19 patients, (2) antibody development and technology, (3) drug analysis and activity, and (4) the study of protein related to Covid-19. These findings could be useful to improve knowledge and understanding, also give direction and potential unexplored biotechnological area for further research.